Multiple lines of evidence reveal a new species of Krait (Squamata, Elapidae, Bungarus) from Southwestern China and Northern Myanmar - Ze-Ning Chen; Sheng-Chao Shi; Gernot Vogel; Li Ding; Jing-Song Shi (ZooKeys, 2021)
Kraits of the genus Bungarus Daudin 1803 are widely known venomous snakes distributed from Iran to China and Indonesia. Here, we use a combination of mitochondrial DNA sequence data and morphological data to describe a new species from Yingjiang County, Yunnan Province, China: Bungarus suzhenae sp. nov. Phylogenetically, this species forms a monophyletic lineage sister to the Bungarus candidus/multicinctus/wanghaotingi complex based on cyt b and ND4 genes but forms a sister species pair with the species B. magnimaculatus Wall & Evans, 1901 based on COI gene fragments. Morphologically, B. suzhenae sp. nov. is similar to the B. candidus/multicinctus/wanghaotingi complex but differs from these taxa by a combination of dental morphology, squamation, coloration pattern, as well as hemipenial morphology. A detailed description of the cranial osteology of the new species is given based on micro-CT tomography images. We revised the morphological characters of B. candidus/multicinctus/wanghaotingi complex and verified the validity of three species in this complex. The distribution of these species was revised; the records of B. candidus in China should be attributed to B. wanghaotingi. We also provide an updated key to species of Bungarus.